The noble gas and nitrogen relationship between Ryugu and carbonaceous chondrites. (15th March 2023) - Broadley, M.W.; Byrne, D.J.; Füri, E.; Zimmermann, L.; Marty, B.; Okazaki, R.; Yada, T.; Kitajima, F.; Tachibana, S.; Yogata, K.; Sakamoto, K.; Yurimoto, H.; et al.
Abstract: Carbonaceous chondrites are considered to have originated from C-type asteroids and represent some of the most primitive material in our solar system. Furthermore, since carbonaceous chondrites can contain significant quantities of volatile elements, they may have played a crucial role in supplying volatiles and organic material to Earth and other inner solar system bodies. However, a major challenge of unravelling the volatile composition of chondritic meteorites is distinguishing between which features were inherited from the parent body, and what may be a secondary feature attributable to terrestrial weathering. In December 2020, the Hayabusa2 mission of the Japan Aerospace Exploration Agency (JAXA) successfully returned surface material from the C-type asteroid (162173) Ryugu to Earth. This material has now been classified as closely resembling CI-type chondrites, which are the most chemically pristine meteorites. The analysis of material from the surface of Ryugu therefore provides a unique opportunity to analyse the volatile composition of material that originated from a CI-type asteroid without the complications arising from terrestrial contamination. Given their highly volatile nature, the noble gas and nitrogen inventories of chondrites are highly sensitive to different alteration processes on the asteroid parent body, and to terrestrial contamination. Here, we investigate the nitrogen and noble gas signature of two pelletized grains collected from the first and second touchdown sites (Okazaki et al., 2022a ), to provide an insight into the formation and alteration history of Ryugu. The concentration of trapped noble gas in the Ryugu samples is greater than the average composition of previously measured CI chondrites and are primarily derived from phase Q, although a significant contribution of presolar nanodiamond Xe-HL is noted. The large noble gas concentrations coupled with a significant contribution of presolar nanodiamonds suggests that the Ryugu samples may represent some of the most primitive unprocessed material from the early solar system. In contrast to the noble gases, the abundance of nitrogen and δ 15 N composition of the two Ryugu pellets are lower than the average CI chondrite value. We attribute the lower nitrogen abundances and δ 15 N measured in this study to the preferential loss of a 15 N-rich phase from our samples during aqueous alteration on the parent planetesimal. The analyses of other grains returned from Ryugu have shown large variations in nitrogen concentrations and δ 15 N indicating that alteration fluids heterogeneously interacted with material now present on the surface of Ryugu. Finally, the ratio of trapped noble gases to nitrogen is higher than CI chondrites, and is closer to refractory phase Q and nanodiamonds. This indicates that Ryugu experienced aqueous alteration that led to the significant and variable loss of nitrogen, likely from soluble organic matter, without modification of the noble gas budget, which is primarily hosted in insoluble organic matter and presolar diamonds and is therefore more resistant to aqueous alteration.